2020
DOI: 10.1101/2020.08.29.273540
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expansion Revealing: Decrowding Proteins to Unmask Invisible Brain Nanostructures

Abstract: Expansion microscopy1,2 is an increasingly widespread technology for nanoimaging, because its precise physical magnification of biological specimens enables ordinary microscopes to achieve nanoscale effective resolutions. Fluorescent labels such as antibodies can be applied either before or after expansion, with the latter offering the potential for better access to proteins within densely packed environments3–7. We here assess this possibility of epitope decrowding through physical expansion of proteins away … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
48
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(55 citation statements)
references
References 52 publications
6
48
1
Order By: Relevance
“…This likely reflects an increased accessibility of their epitopes in the axoneme due its expansion. Such a positive effect of de-crowding due to ExM was previously described in other systems (Sarkar et al, 2020;Tillberg et al, 2016). On the other hand, we observed that two tested antibodies, BBA4 staining the BBs and pBBs in T. brucei (Woods et al, 1989) and mAb62 staining the flagella connector (Abeywickrema et al, 2019) (see also Suppl.…”
Section: Discussionsupporting
confidence: 76%
“…This likely reflects an increased accessibility of their epitopes in the axoneme due its expansion. Such a positive effect of de-crowding due to ExM was previously described in other systems (Sarkar et al, 2020;Tillberg et al, 2016). On the other hand, we observed that two tested antibodies, BBA4 staining the BBs and pBBs in T. brucei (Woods et al, 1989) and mAb62 staining the flagella connector (Abeywickrema et al, 2019) (see also Suppl.…”
Section: Discussionsupporting
confidence: 76%
“…2o; Supplementary Video 1). Additionally, we observed that conventional antigen retrieval protocol is not needed to achieve such an improvement, suggesting expansion may lead to improved accessibility of antibodies to epitopes, which is consistent with a previous report 32 (Fig. 2p-q; Supplementary Fig.…”
supporting
confidence: 91%
“…Other proteins that might comprise the priming filaments include Munc13-1, Munc18-1, and the CAPS family of proteins, all of which stabilize vesicles in the primed state (29,37,38). Rab3-interacting molecule (RIM) mediates the interaction of synaptic vesicles with calcium channels embedded in the presynaptic membrane and has also been identified as a tethering filament (18,39). In all cases, the shortening or zippering of these candidate tethering molecules could enhance the probability of neurotransmitter release.…”
Section: Discussionmentioning
confidence: 99%